Managing change - Heller, Robert (Essential Managers., 1998)
Helps to learn what you need to know about successful delegation from deciding which tasks to delegate and selecting an appropriate candidate to ensuring the brief is clear and the task is carried out to your satisfaction. This title shows you how to free your time and motivate your staff and provides practical techniques to try when delegating.